Pelestarian Seni Budaya Daerah Sasak melalui program ekstrakulikuler - Baiq Hikmah Widiawati; Noor Hasim; Hary Murcahyanto (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2022)
The preservation of traditional Sasak cultural arts for students in the current era has begun to weaken along with advances in virtual world technology, impacting students' creativity and their regeneration system. Sasak traditional cultural arts need to be preserved through activities in schools, namely extracurricular activities involving teachers, coaches, and students. This activity aims to realize the efforts to preserve the arts and culture of the Sasak region and to realize the creation and regeneration of the Sasak cultural arts. Mentoring activities were carried out from January to April 2019 at SMP Negeri 2 Selong. This activity was attended by art teachers and extracurricular teachers of Gendang Beleq traditional music and dance accompaniment. Participants in this activity are all students of grades VII and VIII who take extracurricular programs in the field of arts and culture. The result of this activity is that the effort to preserve the Sasak cultural arts through this activity is said to be successful because of the increasing number of participants' interest in participating in extracurricular activities from the first month of activity to the end of the activity. Efforts to create and regenerate the arts culture of the Sasak area are said to be successful because they are realized in the form of performances, all of which are created by students during the training process in extracurricular activities. This activity concludes that adding the Gendang Beleq extracurricular and the accompanying dance gives its color to fostering regional arts in schools. Interest in traditional dance is increasing rapidly along with the number of enthusiasts in the extracurricular activities of Gendang Beleq music. The power of creativity and regeneration can be realized if the art coaches always bring their students closer to traditional arts and provide opportunities to show their work through performances